Analysis of Basic Cinematography Component in The Short Film “Tilik” Directed by Wahyu Agung Prasetyo - Halimatus Sya’diyah; Asidigisianti Surya Patria (Universitas Multimedia Nusantara, 2023)
Tilik is one of the short Indonesian drama films produced by Ravacana Films in 2018. From its visual appearance, almost 90% of its length dominantly show scenes of getting on a truck on the way to the hospital, and only interspersed with scenes of stopping at the mosque, and road. However, this film managed to become a trending topic in 2020. This film is also one of the short film categories that has successfully obtained achievements from the audience and awards at film festivals. Therefore, the purpose of this study is to analyze how the basic visual components of cinematography in Tilik's short films uses Bruce Block theory. This research uses qualitative descriptive methods, or methods used to search, collect, analyze research data and are presented in descriptive form. Through this method, Tilik is analyzed with a scientific approach to identify how the basic visual components of cinematography is used according to Bruce Block's theory by observing the elements that make up the film. The results of this study show that the seven basic visual components of this Tilik short film are fulfilled. The results of this study show that the seven basic visual components of this Tilik short film are met. With the fulfillment of the basic visual component of the film, it is able to make the film more interesting and comfortable to look at, as well as being able to affect mood. Keywords: basic visual; components; cinematography; tilik; film